The effect of sensory marketing on repurchase intention with Consumer satisfaction as a mediation variable (Study on Restaurant McDonald's Indonesia) - Najib Bahratama; Mahrinasari; Roslina (International Journal of Economics, Business and Innovation Research, 2026)
This research aims analyzing marketing influence sensory to repurchase intention with consumer satisfaction as a mediating variable on McDonald's restaurant customers in Indonesia. Marketing sensory, which includes element sight, sound, smell, taste, and touch, are seen as an important strategy in creating experience holistic consumers so that it can influence satisfaction and behavior purchase repeating. In the middle increasing competition industry food fast serving and decreasing brand awareness of McDonald's Indonesia, this approach is considered relevant For evaluated empirically. This study uses approach quantitative through questionnaire survey to consumers who have do purchases in the last three months. Data analysis was performed using assisted Structural Equation Modeling (SEM) method SmartPLS 3.2.9 for test direct and indirect relationships between variables. Research results shows that all element marketing sensory influential positive and significant on customer satisfaction, while customer satisfaction has an effect positive to intention to repurchase. Apart from that, there is a significant indirect effect between marketing sensory and repurchase intention through satisfaction as a mediating variable. This finding confirms that the marketing strategy Effective and consistent multisensory can improve customer loyalty through increased satisfaction with experience. Theoretically, this research expands understanding about marketing based experience in developing country contexts, as well give implications practical for McDonald's Indonesia in designing a sensory strategy oriented towards customer satisfaction and retention.